A Joint Sub-Channel and Power Allocation Algorithm in Co-Channel Heterogeneous Femtocell Network - Geng Chen; Wenjing Yao; Yinjing Guo; Weiwei Xia (Dianxin kexue)
A joint sub-channel and power allocation algorithm was proposed to suppress co-channel interference. Power control and handover mechanism could be used to suppress the co-channel cross-tier and intra-tier interference achieved by the power allocation for MU and joint sub-channel and power allocation for FU. Mathematically, the cross-tier handover was formulated as optimizing the network throughput under the constraints of each tier target outage probability and the interference-aware resource allocation was formulated as optimizing the sum rate of FU subject to the constraints of the target data rate of handover MU and interference thresholds to other MU and FU. Theoretical analysis and simulation results show that the sum rate of FU can be increased greatly. Meanwhile, the femtocell network capacity and the number of deployable femtocells can also be improved.